PENGARUH CAPITAL ADEQUANCY RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, LOAN TO DEPOSIT RATIO, PROFITABILITAS DAN RISIKO PASAR TERHADAP HARGA SAHAM PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Stanley Matius Danny Tarigant; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2022)
The stock price is used as an assessment by investors related to the success of a company which is often associated with the value of the company. High stock prices make the value of the company also high. A high company value will make the market believe not only in the company's current performance but also in the company's prospects in the future. This study aims to examine and obtain empirical evidence of the effect of car, bopo, ldr, profitability and banking market risk on stock prices in commercial bank companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research population is Commercial Bank Companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample in this study were 38 companies that were included in the Commercial Bank Company which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is linear regression analysis. The results showed that car, ldr, profitability had a positive and significant effect on stock prices. Meanwhile, Bopo, banking market risk has a negative and significant effect on stock prices. Further research can develop this research by using other variables that theoretically have an influence on stock prices such as profitability, leverage, firm size, managerial ownership, liquidity, dividend policy, capital structure, and others.